Integration of ethnoscience and science in making banana cake as a learning media - Amanda, Tania; Kencanawati, Indah; M, Novinovrita (JPBIO (Jurnal Pendidikan Biologi), 2024)
Banana cake is a type of processed food found among the people in Air Bungkal Village, Hamparan Rawang District, Sungai Penuh City which has developed into a business that can be used as a source of income. The purpose of this study is to analyze and transform the original knowledge of a group or community into scientific knowledge with the concept of science so that it can be a learning medium in biology learning in the community of Air Bungkal Village, Hamparan Rawang District, Sungai Penuh City. The method used in this study is a qualitative method with an exploratory approach with a research flow, namely observation, interviews, and documentation carried out in depth. The results of the study showed that there were several stages in the process of making bananas, starting from the selection of raw materials, processing raw materials, mixing, printing, baking, cutting, decorating with candied fruit, and packaging. The process of processing bananas into banana cakes transforming community knowledge into scientific knowledge with the concept of science can be used as a learning medium in biology that can be implemented for further research.